Use of cone-beam tomography and digital subtraction radiography for diagnosis and evaluation of traumatized teeth treated with endodontic surgery and MTA. A case report - Carvalho, Fabíola Bastos de; Gonçalves, Paloma Souza; Lima, Regina Karla de Pontes [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Rasquin, Luis Cardoso; Tanomaru-Filho, Mário [UNESP] (Wiley, 2013)
The aim of this paper was to report the diagnosis and evaluation of periradicular bone repair by using computed tomography and digital subtraction radiography in an endodontic surgery case treated with mineral trioxide aggregate (MTA). The patient had local swelling and fistula 7years after trauma in the upper jaw. Periapical lesion on tooth #12 and root resorption of tooth #11 were detected radiographically. Endodontic therapy and placement of intracanal medication were carried out. After 3months, with no improvement in the clinical signs and symptoms, computed tomography was performed, showing extensive apical bone resorption on tooth #12 and dental resorption promoting communication of the root canal with the periodontium of tooth #11. The patient was referred to endodontic surgery. After surgery and postoperative periods of 15, 30, 60, 90, and 120days, standardized radiographs were taken, digitized, and subjected to digital subtraction of the images using Adobe Photoshop CS software. Four years later, a cone-beam computed tomography was performed, showing bone repair and absence of root resorption at tooth #11. In this clinical case, digital subtraction radiography was effective for early detection of new bone formation and evolution of repair. © 2011 John Wiley & Sons A/S.